The main influencing factors of customer satisfaction and loyalty in city express delivery - Lei, Zheng; Duan, Huawei; Zhang, Liping; Ergu, Daji; Liu, Fangyao (Frontiers in Psychology, 2022)
At present, customers’ low satisfaction and loyalty to city express service have restricted the development of city express. It is particularly important to analyze the factors causing customers’ low satisfaction and loyalty, which will promote the development of city express industry effectively. Based on SERVQUAL model and CCSI model, this paper constructs a new evaluation index system from the perspective of service quality. Through this new system, this paper first explores the factors that affect customers’ satisfaction and loyalty respectively by fuzzy analytic hierarchy process (AHP) and hierarchical regression analysis, taking the expected and perceived service quality as conversion variables. And then it analyzes the common factors that affect customers’ satisfaction and loyalty comprehensively. These two analyses will provide reference for solving the problem of low customer satisfaction and loyalty of city express enterprises. The results show that popularity and credibility, delivery time commitment, and mailing security are the common main factors affecting customer satisfaction and loyalty. Easy-to-understand receipts, the three-level index corresponding to the empathy dimension, is the most significant factor affecting customers’ loyalty in city express industry; Delivery time commitment, the three-level index corresponding to the reliability dimension, is the most significant factor affecting customers’ loyalty in city express industry.